Manutenção forçada de contratos empresariais de longa duração na recuperação judicial - Bonini, Paulo Rogério (2024)
Contract law underwent a relevant reinterpretation in the 20th century, particularly in the face of the phenomenon of mass contracting with consumers and the specialization of the relationship established between companies. The latter began to show a special form of organization of economic activity through various business contracts, deviating from the punctual contract of exchange that inspired the great codifications. It affirms a departure from the theory of will as a justifying element of business relations, attributing greater relevance to the economic element in business relations, which become objective. Accepting the existence of a business contract stricto sensu, focused on the form of organization of the firm and not on the logic of contracts of simple asset exchange, its own characteristics are recognized: long duration, incomplete and relational character, contractual asymmetry and, in some cases, economic dependence. Because they involve the company's own organization or way of being, business contracts stricto sensu have a value of their own distinct from their object, characterizing a relevant asset. In situations of financial or economic crisis, the use of judicial reorganization cannot be seen as an unlawful act in a broad sense, and it is a finalistic and economic contradiction to allow the unilateral breach of the contract essential to the continuity of the company, especially because it is an economic asset and not a simple relationship. First, because the bundles of contracts are a means of organizing the modern company, there would be destruction of its structure by seeking its economic reorganization. Second, because the approval of the reorganization and the approval of the plan means a relative presumption of economic capacity to pay the debts novated by the plan, the pre-existing extra-bankruptcy debts and those resulting from the continuity of the economic activity of the company in crisis. In these cases, the exercise of the right to terminate based on an ipso facto clause based on the request for reorganization or the right to terminate contracts for an indefinite period must be subject to the existence of just cause, under penalty of imposing disproportionate losses on the company under reorganization, in addition to making its recovery unfeasible. On the other hand, the maintenance of the contract in favor of the company in crisis cannot mean the transfer of its economic risks of the business activity to the other party, prevailing the right to terminate or adjust the contract when disproportionate damage in its continuity is demonstrated. The judicial decision that will analyze the legality of the exercise of the right to terminate the contract against the company under reorganization must consider the economic operation represented by the contract, maintaining it for the period of judicial monitoring of the reorganization, provided that the economic interest of the opposing party is maintained, which is presumed to be intact by the maintenance of future contracts in the event of judicial reorganization of the company. The modification of any content must be limited only to the extension of the contract or to meet the specific need of the opposing party, allowing the continuation of the contract without the transfer of losses to the other party.